Joint Fact-Finding in Practice: Review of a Collaborative Approach to Climate-Ready Infrastructure in Rotterdam - Schenk, Todd; Vogel, Ruben A.L.; Maas, Nienke; Tavasszy, Lóránt A. (European Journal of Transport and Infrastructure Research, 2016)
Joint fact-finding has been advanced as a method for helping stakeholders grappling with technically intensive policy and planning challenges to collaboratively engage in research and arrive at shared sets of facts to inform their decision-making. This paper introduces joint factfinding and considers its application in the context of infrastructure stakeholders aiming to assess and increase the resilience of their infrastructure systems to climate change. A set of evaluative criteria is introduced, which are proposed for assessing joint fact finding processes both procedurally and substantively in terms of the outcomes, considering them to be both arenas for collaborative governance and joint knowledge production efforts. These criteria are applied to a case in Rotterdam, the Netherlands. This case suggests that joint fact-finding can provide value, but also reveals some lessons. For the efforts themselves, these lessons relate to: The practical applicability of the outcomes; the inherently contingent nature of the outcomes when addressing wicked problems; questions of representation from stakeholder groups; and the importance of leadership and good process design. The following observations are made regarding the criteria: While they are typically interdependent, both process and outcomes should be evaluated; and more attention should be paid to the method and metrics of evaluation, while recognizing that there is no single formula or approach that can be applied, given the heterogeneity of the criteria.